Factors Associated with Hospital Length of Stay among VTE Cases: Insights from the i-RegVed Registry - Sumit Aggarwal; Peteneinuo Rulu; Heena Tabassum (SAGE Publishing, 2024)
Introduction: Venous thromboembolism (VTE) is a multifactorial condition and one of the leading causes of mortality and disability. The present study explores the factors associated with hospitalization duration among different types of venous thromboembolism diagnoses, such as deep vein thrombosis (DVT), pulmonary embolism (PE), and other forms of thrombosis. Methods: The data included participants with VTE admitted to 13 hospitals within pan-India from June 2022 to December 2023 to the i-RegVed registry, where socio-demographic data, clinical history, and various factors associated with hospital length of stay (LOS) were included for analyses. Multilinear regression was performed to explore the factors associated with hospital LOS among VTE conditions such as DVT, PE, forms of thrombosis other than PE and DVT, and all VTE diagnoses. Results: A total of 633 participants were included in the study, with 55% being males, and 28.9% being homemakers. Longer hospital LOS was significantly associated with age (β = −.09, P  < .05), sex (β = 3.21, P  < .05), and non-communicable diseases (β = 3.51, P  < .05) among participants with DVT and among participants with at least one of the VTE diagnoses, age (β = −.12, P  < .001) and anticoagulant use (β = −2.49, P  < .05) was significantly associated. Conclusion: The findings provide insights into the factors influencing hospital outcomes among participants with different types of VTE, highlighting the importance of age and comorbidities in predicting the hospital LOS.